Potential and Strategy for Development of Livestock Areas in Ternate City, North Maluku Province - Fatmona, Sariffudin; Gunawan, Gunawan (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
The purpose of this research is to the development strategy for livestock areas in Ternate City, North Maluku Province. The data input method is direct observation in the field and through Focus Group Discussion (FGD) techniques as well as data from related agencies and other literature. The analysis used: Location Quotient, Livestock Capacity, and Livestock Concentration Index. For strategic analysis, the SWOT analysis method is used. The results of the Location Quotient (LQ) analysis of poultry on the island of Ternate show that the commodity is quail which has the highest LQ value of 53.07, the commodity of broiler on the island of Ternate with an LQ value of 1.15 indicates potential for livestock development. Based on the results analysis of Batang Dua sub-district/Island had a higher average weight of fresh forage for fodder (1.65 kg = 28%), than Moti sub-district (1.42 kg = 25%), Hiri (1.42 kg = 25%) and Ternate (1.28 kg = 22), the livestock concentration index for cattle commodities by island/district shows that all sub-districts/islands in the city of Ternate are in the category of rare or minimal livestock concentration, namely IKT <1, so it has great potential for development.